Collection development plan and policy for the Arayat Central Elementary School library - Manabat, Elisa Joan S. (2015)
This study was conducted to help the Arayat Central Elementary School, one of the leading primary schools in Pampanga, to have a functioning library. A total of 140 respondents (120 students and 20 teachers) were surveyed to determine the needs and interests of the future clientele. An interview with the principal was conducted separately.